Indução do parto em gravidezes gemelares vs gravidezes únicas: revisão sistemática - Fernandes,Ana João da Silva (2019)
To determine if the induction of labor in twin pregnancies is associated with greater risk of cesarean delivery than the induction of labor in single pregnancies, we performed a systematic review. Only in one of three studies included cesarean delivery after induction is more frequent in twin than in single pregnancies. Through a multivariable analysis, maternal age and nulliparity are more important risk factors to cesarean delivery than twin pregnancy. Twin pregnancies have a higher risk of cesarean delivery than single pregnancies, but this does not appear to be related with induction of labor.